Proceedings of the ACM International Conference Companion on Object Oriented Programming Systems Languages and Applications Com 2011
DOI: 10.1145/2048147.2048186
|View full text |Cite
|
Sign up to set email alerts
|

Moving back to scrum and scaling to scrum of scrums in less than one year

Abstract: We report on the experience of re-introducing Scrum in a project team that had previously failed to adopt that agile method. We explore the reasons we believe that caused the failure and explain how we approached the team to uncover them. Then, we describe our strategy to avoid incurring in those problems again and to take the team to a higher level of productivity, quality and personal satisfaction. We also present the motivation and the actions taken to go further and scale this scenario to multiple feature-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Study 1 [42] reported that adoption of Scrum resulted in quick releases for customers to test. S3 [34], S5 [39] and S6 [23] reported an increase in productivity and quality. The factors leading to increased productivity were listed as increased team velocity, teams with mixed high skills, anchored methodology, improved motivation, business and user involvement, colocation, good infrastructure and frequent communication.…”
Section: Rq4: What Changes Are Required To the Original Scrum Framework To Make It Adaptable To Large Projects And What Effect Does That mentioning
confidence: 94%
See 4 more Smart Citations
“…Study 1 [42] reported that adoption of Scrum resulted in quick releases for customers to test. S3 [34], S5 [39] and S6 [23] reported an increase in productivity and quality. The factors leading to increased productivity were listed as increased team velocity, teams with mixed high skills, anchored methodology, improved motivation, business and user involvement, colocation, good infrastructure and frequent communication.…”
Section: Rq4: What Changes Are Required To the Original Scrum Framework To Make It Adaptable To Large Projects And What Effect Does That mentioning
confidence: 94%
“…The study 5 [39] showed successful adoption of Scrum of Scrums by scaling team to multiple feature oriented teams. They demonstrated that separating teams by feature was perfect in order to focus on the main priorities for the development of the product and to avoid conflicts in backlog management.…”
Section: Sos Reviewsmentioning
confidence: 97%
See 3 more Smart Citations